3(x-1)+3=13

Simple and best practice solution for 3(x-1)+3=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)+3=13 equation:


Simplifying
3(x + -1) + 3 = 13

Reorder the terms:
3(-1 + x) + 3 = 13
(-1 * 3 + x * 3) + 3 = 13
(-3 + 3x) + 3 = 13

Reorder the terms:
-3 + 3 + 3x = 13

Combine like terms: -3 + 3 = 0
0 + 3x = 13
3x = 13

Solving
3x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '3'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| 5x+6=5(x+7) | | 5x-25=26+2x | | 4×3/8 | | (8-3x)/(2√(4-x)) | | -10r=-40 | | 13-9x=26-16x | | 9=-(r-5)+1 | | x^2+4n+4=0 | | 6z=-117 | | 42+4y-11=12y-11-2y | | (2w-9)(w)=110 | | (5x+4)=0 | | 8x-27+5x+18=180 | | 22+3y-6=11y-9-3y | | 17+X=22.3 | | -2x+3=7x-5 | | 0=950x^5/2 | | 6x+-5=2x+3 | | (x+3)(x-2)=2x | | 3.428571429*14=x | | 1/4(x-3)=-2 | | 23000=mx+0.05 | | 5n-6n=18 | | 7(x-4)=16+32x | | 1/(2v^-2) | | an=550+(-50)(n-1) | | x^2+144=20 | | 1/2v-2 | | an=100+(-20)(n-1) | | 25x+x+3=90 | | 7x+1+108=180 | | -7/10+-5/12-1/4= |

Equations solver categories